2021
DOI: 10.1016/j.ijrobp.2021.07.666
|View full text |Cite
|
Sign up to set email alerts
|

Focused Ultrasound-Mediated Blood-Brain Barrier Opening Enhances Panobinostat Efficacy in a Murine Diffuse Intrinsic Pontine Glioma Model

Abstract: AAPM TG 132. The mean score was below 1.0 for all volumes. Editing thecal sac and vertebrae auto contours only required 1 min or less for all patients. The models reduced contouring time by 84 and 40 min for thecal sac and vertebrae, respectively. Conclusion:The deep-learning models provided high-quality auto contours, directly acceptable for lungs and requiring only minor editing in less than one min for thecal sac, vertebrae and kidneys. Given the labor-intensive nature of manually contouring thecal sac and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Preclinical studies remain limited by the ability of HDACis to consistently traffic across the blood-brain barrier and into tumor, particularly into the pons and it is a limitation of this study to rely on flank model systems, though we believe this does support biological anti-tumor activity of the drug in vivo . The observed efficacy of quisinostat in this study further supports generation of blood-brain penetrating versions of quisinostat as well as continued development of drug conjugates and enhanced locoregional delivery systems such as intra-ommaya approaches used in locoregional CAR T cell trials [42] , intra-pontine approaches used in convention-enhanced delivery (CED) trials [43] or strategies to increase the permeability of the blood-brain barrier to enhance penetrance of HDACi [44] . Other preclinical work has shown benefit of blood brain barrier penetrant quisinostat [45 , 46] and hopefully can be preclinically evaluated in future orthotopic xenograft and genetically-induced models of DIPG.…”
Section: Discussionsupporting
confidence: 52%
“…Preclinical studies remain limited by the ability of HDACis to consistently traffic across the blood-brain barrier and into tumor, particularly into the pons and it is a limitation of this study to rely on flank model systems, though we believe this does support biological anti-tumor activity of the drug in vivo . The observed efficacy of quisinostat in this study further supports generation of blood-brain penetrating versions of quisinostat as well as continued development of drug conjugates and enhanced locoregional delivery systems such as intra-ommaya approaches used in locoregional CAR T cell trials [42] , intra-pontine approaches used in convention-enhanced delivery (CED) trials [43] or strategies to increase the permeability of the blood-brain barrier to enhance penetrance of HDACi [44] . Other preclinical work has shown benefit of blood brain barrier penetrant quisinostat [45 , 46] and hopefully can be preclinically evaluated in future orthotopic xenograft and genetically-induced models of DIPG.…”
Section: Discussionsupporting
confidence: 52%
“…Several groups have looked into this technology to deliver drugs to solid tumors. Some of these trials have shown increased survival and reduced tumor growth 23,35,[48][49][50][51][52][53][54][55][56][57] 54,57,58 .…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, this technology has been translated into clinical trials showing the safety of FUS/MB treatments, and current clinical trials are focused on efficacy with tumor types other than DIPG, including glioblastomas. Due to the depth and targeting complexity of the brainstem, only a few groups have investigated using this technology for pontine DMG54,55,[57][58][59] . Over the last 5 years, two groups have looked into using MRI-guided FUS/…”
mentioning
confidence: 99%